Looking beyond satisfaction: evaluating the value and impact of information skills training. (March 2015) - Raynor, Michael; Craven, Jenny
Abstract In this feature guest writers Michael Raynor and Jenny Craven from the National Institute for Health and Care Excellence (NICE) present an overview of their evaluative research study on the value and impact of the information skills training courses they provide at NICE. In particular, this small study used a combination of qualitative and quantitative data to look beyond satisfaction and confidence levels and identify whether learning had actually taken place as a result of attending the sessions, and how new skills were used by the attendees in their day‐to‐day work. H.S.